INFLUÊNCIA DA ADUBAÇÃO ORGÂNICA NAS DIFERENTES DENSIDADES POPULACIONAIS DE RÚCULA CONSORCIADA COM RABANETE - BARROS FILHO, Luís Gustavo Silva; SILVA, Maiele Leandro da; MARCELINO, Adriele Ferreira; LLEGRETTI NETO, Alberto Renato; GOMEZ, Aurélio Luis Carpinedo (ANAIS DO ENIC, 2024)
-